2011
DOI: 10.1089/ars.2010.3657
|View full text |Cite
|
Sign up to set email alerts
|

Peroxiredoxins in Plants and Cyanobacteria

Abstract: Peroxiredoxins (Prx) are central elements of the antioxidant defense system and the dithiol-disulfide redox regulatory network of the plant and cyanobacterial cell. They employ a thiol-based catalytic mechanism to reduce H 2 O 2 , alkylhydroperoxide, and peroxinitrite. In plants and cyanobacteria, there exist 2-CysPrx, 1-CysPrx, PrxQ, and type II Prx. Higher plants typically contain at least one plastid 2-CysPrx, one nucleo-cytoplasmic 1-CysPrx, one chloroplast PrxQ, and one each of cytosolic, mitochondrial, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
293
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 347 publications
(312 citation statements)
references
References 186 publications
8
293
0
1
Order By: Relevance
“…However, this is not the case for 2-cys peroxiredoxins, in which the sulfinic form of the catalytic cysteine can be reduced to the sulfenic acid form by proteins such as sulfiredoxin or sestrin (14)(15)(16).…”
Section: Gsh and Redox Signallingmentioning
confidence: 99%
“…However, this is not the case for 2-cys peroxiredoxins, in which the sulfinic form of the catalytic cysteine can be reduced to the sulfenic acid form by proteins such as sulfiredoxin or sestrin (14)(15)(16).…”
Section: Gsh and Redox Signallingmentioning
confidence: 99%
“…In defence against toxic Aquat Ecol (2016) 50:443-460 449 reactive oxygen species (ROS), green algae possess a wide repertoire of superoxide and peroxide neutralizing enzymes and the complementary reducing substrates. Examples include the co-substrate-dependent enzymes ascorbate oxidase and thioreductase, next to the reducing co-substrate-independent superoxide dismutase and catalase enzymes (Dietz 2011;Schmitt et al 2014). The possible algicidal and cyanocidal and/ or cyanostatical activity of HP as formed during decay of barley and rice straw have been mentioned already in ''Barley straw'' and ''Rice straw'' sections of this review.…”
Section: Hydrogen Peroxidementioning
confidence: 99%
“…Studies of bacteria, plants, and animals revealed that ROS signals could be perceived directly by specific sensors (Storz et al, 1990;D'Autréaux and Toledano, 2007) or by the use of antioxidative enzymes, such as peroxiredoxins (Prxs) (D'Autréaux and Toledano, 2007;Fourquet et al, 2008;Dietz, 2011;Fomenko et al, 2011). Prxs are ancient conserved enzymes that catalytically reduce hydrogen peroxide and organic peroxides and in turn oxidize their electron donors, such as Trxs, to regenerate their activity (Hall et al, 2009;Dietz, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Prxs are ancient conserved enzymes that catalytically reduce hydrogen peroxide and organic peroxides and in turn oxidize their electron donors, such as Trxs, to regenerate their activity (Hall et al, 2009;Dietz, 2011). Plant Prxs were implicated as redox sensors, linking the redox signaling and ROS networks of cells (Dietz, 2011). Recent findings identified particular 2-Cys Prxs as a circadian rhythmic biomarker in algae cells and mammalian red blood cells and as a regulator of Drosophila melanogaster embryo development (Degennaro et al, 2011).…”
Section: Introductionmentioning
confidence: 99%